(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
The objective of this paper is studying Lie group G(X) on algebra X and define two norms in this algebra and give some properties of two-norm algebras which are topological, and relate some concepts with the topological notions introduced by A. Alexiwicz [1]. إن الهدف من هذا المقال هو دراسة زمرة لي G(X) في الجبر X وتعريف نظيمين في هذا الجبر ودراسة بعض الخصائص للجبور ثنائية النظيم التي هي بحد ذاتها فضاء تبولوجي وربط بعض المفاهيم الجبرية بالمفاهيم التبولوجية وأن هذه الدراسة تعتبر تعميما للجبور ثنائية النظيم المعرفة من خلال A. Alexiwicz [ 1] حيث بنيت في هذا المقال على زمر لي.